Sustainability aspects of participatory budgeting at the municipal level in Slovenia (Public Sector Economics - submission site, 2022)
The Local Self-Government Act has given explicit legal ground for the use of optional participatory budgeting (PB) on the municipal level in Slovenia since 2018. This means municipalities and their inhabitants have absolute discretion regarding the nature of proposed and later (if chosen) implemented projects in a certain municipality if the projects fall under municipal authority. The article presents research results that reveal that a legislative soft approach to PB, resulted in small municipal engagement in PB projects. They on average spent up to one percent of budgetary expenses for PB purposes, resulting mostly in inclusive, peoplecentered projects promoting facilities for socializing, and different kinds of public infrastructure capacities (sports infrastructure, etc.). The projects implemented in Slovenia so far are prevailingly “public infrastructure projects” in line with the municipal social sustainability agenda promoting equality and diversity, social cohesion, democracy and governance, and quality of life in a certain municipality.